2013
DOI: 10.1093/humrep/det392
|View full text |Cite
|
Sign up to set email alerts
|

In young men sperm telomere length is related to sperm number and parental age

Abstract: This work was supported by the Italian Ministry of University and Research (grant no. 2009AMPA9C to C.F.) and Padova University (grant 2010 to A.D.R.). The authors have no competing interests to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 31 publications
6
86
5
1
Order By: Relevance
“…Moreover, STL is related to sperm count. However, the relationship between LTL and sperm count did not demonstrate a significant correlation [27] . Considering the role of telomeres in meiosis and maintenance of genome integrity, the telomere shortening might lead to impaired spermatogenesis, followed by germ cells death.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Moreover, STL is related to sperm count. However, the relationship between LTL and sperm count did not demonstrate a significant correlation [27] . Considering the role of telomeres in meiosis and maintenance of genome integrity, the telomere shortening might lead to impaired spermatogenesis, followed by germ cells death.…”
Section: Discussionmentioning
confidence: 84%
“…Our results showed that there was a promising association between telomere length and the occurrence of azoospermia even if the telomere size was evaluated in the blood leukocytes of azoospermic males. In a study by Ferlin et al [27] it has been found that LTL was significantly correlated with SLT. Moreover, STL is related to sperm count.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…While most of the studies evaluated the relationship between paternal age and leucocytes telomere length, the positive correlation between paternal age and offspring sperm telomere length was for the first time reported in 2013 by a study evaluating a small sample (81 subjects) of young men (18-19 years old) [73]. However, in this study, the maternal age was also positively correlated to sperm telomere length, and the contribution of each parents' age was difficult to established due to the high correlation between parents age.…”
Section: Telomere Lengthmentioning
confidence: 99%